The Influence Of Training And Work Motivation Work Motivation On The Effectiveness Of Performance Of Employees Of The Regional Office Of The Directorate General Of Customs And Excise Jakarta - Taufik, Imam; Sodirin, Sodirin (Multidisciplinary Journals, 2025)
The Regional Office of the Directorate General of Customs and Excise in Jakarta has recently come under public scrutiny due to various issues, including allegations of corruption and dissatisfaction among business operators regarding the services provided, which indicate problems in employee performance effectiveness. The implementation of training programs and the low work motivation of employees have also affected work outcomes, as evidenced by delays in program completion and poor adherence to attendance standards. This study is crucial for understanding how training and work motivation can enhance employee performance effectiveness, contributing to the optimal achievement of organizational goals. This research will be conducted at the Regional Office of the Directorate General of Customs and Excise in Jakarta from May to July 2024, using a quantitative descriptive approach. The location was chosen for its relevance to the research focus, which aims to examine the influence of training and work motivation on employee performance effectiveness. The research sample consists of 22 respondents, with training (X1) and work motivation (X2) as independent variables, and employee performance effectiveness (Y) as the dependent variable. The analysis results show that training (X1) has a 58.7% influence on employee performance effectiveness at the Regional Office of the Directorate General of Customs and Excise in Jakarta, while work motivation (X2) has a 39.3% influence. Simultaneously, both variables affect employee performance effectiveness by 44.2%.